Mma Exercises in Physical Education of 17-18-Year-Old Students - GEORGIEVNA, TODOROVA VALENTYNA (2021)
In modern science there is a permanent search for new effective forms of organization of the educational process in physical training at higher education institutions of different orientation. The article presents a solution of the actual scientific and practical task of improving the level of physical fitness of students and increasing the readiness of young people of military age to fulfill their national service obligation and advancement of the content of physical education in agrarian institutions of higher education by means of the program of sectional classes using the means of MMA. Due to the conducted research, for the first time, the structure and content of the program of sectional classes with the priority use of means of MMA all-around in physical education of students of institutions of higher education has been scientifically substantiated; the effectiveness of the use of means of military sports all-around for students of agricultural institutions of higher education was determined by indicators of their physical condition, physical development, functional and psychological state, physical fitness. The effectiveness of the author’s program is confirmed by the improvement of functional capabilities, normalization of physical condition, enhancement of the level of physical fitness, increase of interest of young men to engage in physical education and importance of instrumental and terminal values.